The World Alliance for Patient Safety (Italian Journal of Public Health, 2005)
Despite enormous strides in our knowledge about quality health services, and the continuously growing interest in the safety of patients among policy makers and clinical leaders, much remains to be done to avoid unintentionally harm occurring in health care. In May 2004, the Fifty-seventh World Health Assembly supported the creation of the World Alliance for Patient Safety which aims to coordinate, spread and accelerate improvements in patient safety worldwide. The Forward Programme 2005 of the World Alliance for Patient safety sets out an important and comprehensive programme of international work in areas such as reporting and learning, patient involvement and safety solutions. The experience of other high risk industries, suggests that patient safety problems are primarily a function of deficiencies in system design, organization and operation. Understanding and improving the design of processes, structures and culture of health care delivery is therefore central to making care safer. A number of core challenges emerge across many European countries including the need to continue to build strong political will and commitment to address patient safety problems, stronger engagement and leadership from health care professionals, and promoting positive cultural changes with health care.
Keywords: Patient safety; adverse events; systems